Apical Hypertrophic Cardiomyopathy and Multiple Coronary Artery-Left Ventricular Fistulas: A Case Report. - Ruggiero Massimo; Tota Francesco; Sassara Marco; Locuratolo Nicola; Calvani Vito; Dentamaro Ilaria; Tesorio Maria; Scicchitano Pietro; Caldarola Pasquale; Matteo Ciccone Marco (Journal of Hypertension and Cardiology, 2013)
We describe a rare case of multiple coronary artery-left ventricular fistulas associated with apical hypertrophic cardiomyopathy in a 62 year asymptomatic old male admitted to our department for a perioperative evaluation of non cardiac surgery, already diagnosed for multiple coronary artery-left fistulae. He underwent transthoracic echocardiography and then to accelerated dipiridamole stress-echo.
Keywords: coronary artery left-ventricular fistulae